ASSESSMENT OF THE ECOLOGICAL STATUS OF NEVĖŽIS RIVER - Petraškienė, Violeta; Nesovas, Deividas (PROFESSIONAL STUDIES: Theory And Practice, 2022)
Upon Lithuania’s accession to the EU, water bodies are managed and protected according to hydrologically defined natural river basin boundaries, as the quality of river water is determined by natural processes taking place in the territory of a river basin and the overall impact of economic activities. A river basin is an area from which all surface water flows into a single river. By implementing the requirements of water protection legislation, Lithuania has to achieve good status in all water bodies in the country by 2021. This article discusses the ecological status of Nevėžis river in Nevėžis sub-basin. Summarising all the parameters assessed (BOC7, NO3-N, Pb, Nb, O2, NH4-N bei pH) and assessing the water quality of Nevėžis river according to its ecological classes, it is from average to very good condition. Key words: river basin, Nevėžis river, Nevėžis sub-basin, ecological status of a river.